Formação continuada de professores para a educação básica: desafios na escola pública municipal com alunos com deficiência em Gurupá - Pará - TENÓRIO, Mônica Felipe (2023)
Today society has a more egalitarian view on the most varied topics, it could not be different in the face of the topic "school inclusion of people with disabilities". Much time passed before this issue gained real relevance, but now with changes in thoughts and attitudes towards Persons with Disabilities, society and its rulers have begun to give due value to this issue. Therefore, the present study arises with the objective of analyzing the actions for the Continuing Training of Teachers to work in Basic Education in the Degree in Pedagogy in the face of the daily challenges faced in the Municipal Public School with students with disabilities from Gurupá - Pará. The methodological approach is qualitative in the form of a documentary research. The study will primarily discuss a brief definition about the training of Basic Education teachers and then punctuate "special education and inclusive education", then a historical retrospective will be made regarding the approach of this theme in Brazil, soon after it speaks a little about the programs aimed at this type of education and also what the law provides about the training of education professionals in this type of education, therefore speaking of special education within the scope of the public education network of the municipality of Gurupá and highlights the importance of the pedagogy course for teachers from early childhood education to the early years of elementary school.